2011
DOI: 10.1007/s00380-011-0162-0
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of left ventricular contractility in pediatric patients using the maximum rate of pressure rise in peripheral arteries

Abstract: The maximum rate of left ventricular pressure rise (LV dp/dt(max)) is a good indicator of ventricular contractility. However, its measurement requires invasive cardiac catheterization. By applying the relationship between the ratio of aorta (Ao) dp/dt(max) to LV dp/dt(max) and the mean artery pressure (MAP), we tested the possible noninvasive estimation of LV dp/dt(max) by the maximum rate of pressure rise in peripheral arteries, as measured by tonometry. The study subjects were 31 children with cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…[16] Regarding the utility of dP/dt max as a bedside monitoring, it has been suggested that the Ao dP/dt max is closely correlated with the LV dP/dt max , which means Ao dP/dt max may be potential as a less invasive method to determine LV contractility especially in patients with congenital heart disease. [5] Recently, Kawasaki et al [6] reported that the LV dP/dt max can be estimated noninvasively from brachial or radial arterial pressure waveforms using a tonometry. They also showed that dP/dt max derived from peripheral arteries have significant linear relationships with Ao dP/dt max , despite pressure differences between the measured sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Regarding the utility of dP/dt max as a bedside monitoring, it has been suggested that the Ao dP/dt max is closely correlated with the LV dP/dt max , which means Ao dP/dt max may be potential as a less invasive method to determine LV contractility especially in patients with congenital heart disease. [5] Recently, Kawasaki et al [6] reported that the LV dP/dt max can be estimated noninvasively from brachial or radial arterial pressure waveforms using a tonometry. They also showed that dP/dt max derived from peripheral arteries have significant linear relationships with Ao dP/dt max , despite pressure differences between the measured sites.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Recently, the dp/dt max tonometrically measured at the brachial and radial arteries has also been found to show excellent correlation with the LV dP/dt max in children underwent cardiac catheterization for various cardiovascular abnormalities. [6] Therefore, the peripheral dP/dt max derived from pressure waveform analysis seems to be useful to assess ventricular contractility as a noninvasive intraoperative monitoring, particularly in pediatric cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%